Comparação entre métodos de otimização aplicados aos ajustes de relés direcionais de sobrecorrente - Souza, Luis Antonio Paulino de (2019)
The purpose of this work is to develop a methodology for the comparison of optimization deterministic methods with a semi-empirical, heuristic and hybrid approach applied to obtain optimized values of the pick-up current and time multiple in directional overcurrent relays considering the performance of the distance protection. The model has as input data the limits of the three-phase short-circuit current at the start of the transmission line, the relay pairs to be coordinated, the operative limits of the time multiple, the pick-up current, and the type of curve to be used. The results are obtained in different applications, taking into account the restrictions and validating the results obtained with results from the literature. The proposed methodology presents itself as an efficient tool to aid in the study of protection and selectivity, contributing to the coordination process of directional overcurrent relays and comparing the deterministic, heuristic and hybrid optimization methods applied to two transmission systems.